Importancia del derecho de superficie. Tradición y nuevos retos desde la regulación legal en Italia y su práctica en el Perú - Varsi-Rospigliosi, Enrique (2024)
The surface is an ancient right in rem. Its Roman origins have consolidated it as an effective institution, a clear example of which is the Italian Civil Code, which presents an efficient treatment and should be reflected in the use and execution of this right. The practice in Peru, although it has been consolidating, presents the surface as a right that allows access to land in the urban, commercial and industrial sector.